Effects of aspirin and non-steroidal anti-inflammatory drugs on the risk of cholangiocarcinoma: Ameta-analysis - K. Lapumnuaypol (2020)
© The Author(s) 2019. Background: Non-steroidal anti-inflammatory drugs (NSAIDs) can suppress the proliferation of cholangiocarcinoma (CCA) cells in vitro through inhibition of cyclooxygenase-2. However, the effects of aspirin and NSAIDs on the risk of CCA remain unclear. We performed this meta-analysis to assess the risk of biliary tract cancers in patients who take aspirin and/or NSAIDs. Methods: A systematic review was conducted utilizing MEDLINE, EMBASE, Cochrane databases from inception through October 2017 to identify studies that assessed the association of aspirin and/or NSAIDs use with risk of biliary tract cancers including CCA, gallbladder cancer and ampulla of Vater cancer. Effect estimates from the studies were extracted and combined using the random-effect, generic inverse variance method of DerSimonian and Laird. Results: Five observational studies with a total of 9 200 653 patients were enrolled. The pooled OR of CCA in patients with aspirin use was 0.56 (95% CI, 0.32-0.96). Egger's regression asymmetry test was performed and showed no publication bias for the association between aspirin use and CCA with P = 0.42. There was no significant association between NSAIDs use and CCA, with a pooled OR of 0.79 (95% CI, 0.28-2.21). One study showed a significant association between aspirin use and reduced risk of gallbladder cancer with OR of 0.37 (0.17-0.80). However, there was no significant association between aspirin and ampulla of Vater cancer with OR of 0.22 (0.03-1.65). Conclusions: Our study demonstrates a significant association between aspirin use and a 0.56-fold decreased risk of CCA. However, there is no association between the use of NSAIDs and CCA.